There is no Software, there are just Services - Kaldrack, Irina; Leeker, Martina (Digital Cultures, 2015)
Is software dead? Services like Google, Dropbox, Adobe Creative Cloud, or Social Media apps are all-pervasive in our digital media landscape. This marks the (re)emergence of the service paradigm that challenges traditional business and license models as well as modes of media creation and use. The short essays in this edited collection discuss how services shift the notion of software, the cultural technique of programming, conditions of labor as well as the ecology and politics of data and how they influence dispositifs of knowledge.